2018
DOI: 10.3390/ijms19020363
|View full text |Cite|
|
Sign up to set email alerts
|

Ethanol Extract of Oldenlandia diffusa Herba Attenuates Scopolamine-Induced Cognitive Impairments in Mice via Activation of BDNF, P-CREB and Inhibition of Acetylcholinesterase

Abstract: Though Oldenlandia diffusa Herba (ODH) has been known to exhibit anti-cancer and anti-inflammatory effects, its anti-amnestic effect has never been reported so far. The aim of this present study was to elucidate the anti-amnestic effect of ODH. ODH pretreatment significantly reduced escape latency of scopolamine treated Institute of Cancer Research (ICR) mice compared to untreated control groups in a Morris water maze test. Similarly, the passive avoidance test showed that ODH treatment recovered the scopolami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Scopolamine, a blocker of muscarinic ACh receptors, is used to induce oxidative stress, reduce hippocampal volume, and dysregulate the cholinergic neuronal pathway in rodents and humans [ 7 , 8 ]. In addition, scopolamine reduced the expression of the brain-derived neurotrophic factor (BDNF)/tyrosine kinase (TrkB) signaling pathway, which plays a crucial role in memory processes [ 9 , 10 , 11 , 12 ]. BDNF, a neurotrophic factor, activates TrkB that is a BDNF receptor and enhances synaptic plasticity, memory formation, and the persistence of memory storage [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scopolamine, a blocker of muscarinic ACh receptors, is used to induce oxidative stress, reduce hippocampal volume, and dysregulate the cholinergic neuronal pathway in rodents and humans [ 7 , 8 ]. In addition, scopolamine reduced the expression of the brain-derived neurotrophic factor (BDNF)/tyrosine kinase (TrkB) signaling pathway, which plays a crucial role in memory processes [ 9 , 10 , 11 , 12 ]. BDNF, a neurotrophic factor, activates TrkB that is a BDNF receptor and enhances synaptic plasticity, memory formation, and the persistence of memory storage [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…BDNF, a neurotrophic factor, activates TrkB that is a BDNF receptor and enhances synaptic plasticity, memory formation, and the persistence of memory storage [ 11 , 12 , 13 ]. Hence, approaches to the treatment and prevention of Alzheimer’s disease (AD) have been studied by investigating candidates that possess not only antioxidative effects but also regulate the cholinergic system and the BDNF/TrkB pathway by administering plant-derived extracts to animal models of AD [ 10 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research has demonstrated that scopolamine-induced OS increases the levels of malondialdehyde (MDA) [50,63,[67][68][69]. In line with the earlier study by Hritcu et al [70], ex vivo determination of MDA levels in the brains of cognitive-impaired mice demonstrated high MDA profile in the negative control.…”
mentioning
confidence: 52%
“…In this study, cognitive impairment was induced in experimental mice via the administration of scopolamine, a drug that hinders memory and cognitive functions by blocking muscarinic receptors in the central and peripheral nervous systems [40][41][42]. Scopolamine has been utilized widely to evaluate the potential of drug agents proposed for dementia therapy because it causes symptoms synonymous to those caused by neurodegenerative dementias in a short time [39,[43][44][45][46][47][48][49][50].…”
mentioning
confidence: 99%
“…Since scopolamine is known to show rapid antidepressant effects in humans, and impair short-term memory and learning ability, it has been used for the Alzheimer's disease animal model. 64,65 Therefore, the behavioral memory improvement of WP in scopolamine-induced impairment in memory acquisition in mice was examined. The results are summarized in Table 5.…”
mentioning
confidence: 99%